The relationship between entrepreneurial orientation and employees performance at Johor Corporation in Johor / Nurul Diyana Rozadin - Rozadin, Nurul Diyana (2018)
Generally, this studies was conducted at Johor Corporation in Johor with total of 162 sample size. The purpose of this study is to identify the relationship between entrepreneurial orientation and employee performance at Johor Corporation in Johor. Other than that, this study also intends to identify which dimension of entrepreneurial orientation (innovativeness, proactiveness, competitive aggressiveness, risk taking and autonomy) is most practiced by employees of Johor Corporation in Johor. Along the phase of conducting this study, researcher had used stratified random sampling as the sampling technique. The result of this study shows that there is a significant relationship between entrepreneurial orientation and employee performance at Johor Corporation in Johor. It also shows that the employees of Johor Corporation in Johor practice proactiveness the most. Through this research, researcher will show the data that she obtained from the study that she conducted at Johor Corporation in Johor and how she obtained them